2008
DOI: 10.1007/s10863-008-9187-1
|View full text |Cite
|
Sign up to set email alerts
|

The yeast mitochondrial citrate transport protein: identification of the Lysine residues responsible for inhibition mediated by Pyridoxal 5′-phosphate

Abstract: The present investigation identifies the molecular basis for the well-documented inhibition of the mitochondrial inner membrane citrate transport protein (CTP) function by the lysine-selective reagent pyridoxal 5′-phosphate. Kinetic analysis indicates that PLP is a linear mixed inhibitor of the Cys-less CTP, with a predominantly competitive component. We have previously concluded that the CTP contains at least two substrate binding sites which are located at increasing depths within the substrate translocation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Thus inhibitor binding appears to reduce CTP flexibility, perhaps locking it into one of the conformation(s) that is normally assumed during the transport cycle. The latter point is supported by our earlier findings that each of the inhibitors tested display a strong competitive component in their inhibition mechanism (Remani et al 2008; Aluvila et al 2010). …”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Thus inhibitor binding appears to reduce CTP flexibility, perhaps locking it into one of the conformation(s) that is normally assumed during the transport cycle. The latter point is supported by our earlier findings that each of the inhibitors tested display a strong competitive component in their inhibition mechanism (Remani et al 2008; Aluvila et al 2010). …”
Section: Discussionsupporting
confidence: 76%
“…Finally, PLP is a lysine-selective covalent modification reagent which in the absence of reducing agent forms a reversible Schiff base (Lundblad 1991). We have previously demonstrated that PLP behaves as a linear mixed inhibitor of the CTP, with a predominantly competitive component and displays a K ic of 3.6±0.8 mM (Remani et al 2008). PLP exerts its main inhibitory effect via binding to Lys-83 in binding site 1, and a small effect via binding to residues Lys-37 and Lys-239 in site 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the more than 50 mitochondrial membrane substrate/ion transporters of the SLC25 superfamily that have been identified and characterized to date (for reviews see: Kaplan, 2001;Palmieri and Monné, 2016), Kaplan's laboratory (Remani et al, 2008;Aluvila et al, 2010;Sun et al, 2010;Nie, 2017) has provided significantly detailed information on the structure, substrate transport mechanism and analysis of inhibition by BTC and other potential inhibitors of the citrate-malate CTP carrier, as well as on the PMCT membrane transporter. PMCT is the more recently characterized plasma membrane citrate transporter variant in humans and has garnered considerable attention since it serves as an additional (and, so far only) channel for the influx of citrate into the cytosol from the extracellular space (Mycielska et al, 2009).…”
Section: Control Of Glycolysis and Cholesterogenesis In Tumorsmentioning
confidence: 99%
“…Neither group examined the transport of PLP. Due to the fact that PLP reacts very easily with the amino acid lysine, forming a Schiff's base with the epsilon amino group, PLP is often used in transport assays as an effective inhibitor (Remani et al 2008). Hence, it seems unlikely that Vitamin B 6 is transported in this form, but rather as pyridoxamine or pyridoxine.…”
Section: Transporters Of Coenzymes or Their Precursors For Photorespimentioning
confidence: 99%